Prenatal exposure to antibiotics and risk of childhood overweight or obesity: A systematic review and meta‐analysis. (3rd December 2021) - Solans, Marta; Barceló, Maria A.; Morales‐Suárez‐Varela, Maria; Moya, Andrés; Saez, Marc
Summary: Infant antibiotic use has been modestly associated with childhood overweight, while evidence on prenatal exposures remains less clear. A systematic review and meta‐analysis were conducted to examine associations between maternal antibiotic exposure and subsequent risk of childhood overweight/obesity. Publications were retrieved from PubMed and Web of Science databases up to December 2019. A random effects model was used to summarize risk estimates, overall, and by period and frequency of exposure. Ten observational studies were included in the narrative synthesis. We did not observe a clear pattern of association between prenatal antibiotic use and childhood overweight/obesity. There were suggestive associations for repeated exposures (≥3 courses) and those taking place during the second trimester of gestation, which were also pointed out in our meta‐analysis (relative risk, RR 2T  = 1.15 (95% CI 1.04; 1.28, I 2  = 18%), and RR 3courses  = 1.31 (95% CI 1.03; 1.67, I 2  = 65%), respectively). In most studies, however, confounding by underlying infections cannot be ruled out. Overall, current data do not conclusively support the hypothesis that prenatal exposure to antibiotics is a risk factor for childhood obesity/overweight. Further studies, controlling for underlying infections and exploring the association according to frequency, period (both prenatal and intrapartum) and type of antibiotic, are needed to clarify this association.